Apuntes para reflexionar sobre la hegemonía en el espacio de trabajo - Giniger, Nuria Inés (2012)
Work processes and relationships that unfold at the workplace have often been set aside for the study of hegemonic processes. We propose in this article to focus in some theoretical elements to relocate the production of hegemony in the factory level.